Kritis Terhadap Peranan Ulama Dalam Proses Akulturasi Islam Dan Budaya Lokal - udin, nas nasru (Jurnal Adabiyah, 2015)
This writing critically studies the relation between Islam and Archipelago Local culture base on Islamic and cultural perspective. Based on this writing, there is culture in Islam, and there are Islamic values in culture. Islam needs culture in spreading its mission, either in the form of tradition, art, norms etc. Some ulamas and missionaries in the very early of Islam resurrection in this country realized that the Islamic spreading had to be running peacefully, thus to avoid the conflict between religion and culture, the ulama spread Islamic missing using local wisdom approaches, thus the confrontation between the both could be ignored.